Peningkatan Hasil Belajar Akidah Akhlak Melalui Penggunaan Media Video Pembelajaran Daring Pada Siswa Kelas VII MTS Negeri 3 Pekanbaru - Murni, Tuti (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2022)
This study aims to improve student learning outcomes in the Akidah Akhlak subject through the use of video media for class VII.1 at MTs Negeri 3 Pekanbaru City. The problem raised is that Student Learning Outcomes in Akidah Akhlak Subjects Can Improve Through the Use of Online Learning Video Media for class VII.1 at MTs Negeri 3 Pekanbaru City. The design or design in this research is Classroom Action Research (CAR). CAR is "an observation of learning activities in the form of an action, which is intentionally raised and occurs in a class together." The Classroom Action Research (CAR) procedure begins with the first cycle consisting of four activities, namely: planning (planning), action (acting), observation (observing), reflection (reflecting). There is also the research results obtained information that in the implementation of the first cycle from the results of observations made during the learning process showed that learning activities and student learning outcomes were not optimal. However, there was an increase in learning activities after improvements were made in cycle II and cycle III. From the research results, it can be concluded that the application of the dring method can improve student learning outcomes in class VII.1 MTsN 3 Pekanbaru City.